Filmic discourse and sociocultural dimension in the film Wiñaypacha - Yucra Mamani, Yudi Janeh; Aragón Cruz, Walker Ernesto; Palomino Asqui, Dulio César (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The emerging proposal of author cinema looks to make social contexts and cultural identities visible. Wiñaypacha belongs to this trend, since it is a film recorded entirely in the Aymara language as an expression of the reality and the Andean cosmovision of the Altiplano of Puno (Peru). The purpose of the study is to analyze the film discourse and the sociocultural dimension in the film Wiñaypacha, resorting to qualitative research based on semiotic and content analysis. The film propose an original narrative of 96 planes, it´s silent, reflects ancestral experiences and expose structural problems such as poverty and social exclusion.